Melanosome‐autonomous regulation of size and number: the OA1 receptor sustains PMEL expression. (11th April 2014) - Falletta, Paola; Bagnato, Paola; Bono, Maria; Monticone, Massimiliano; Schiaffino, Maria Vittoria; Bennett, Dorothy C.; Goding, Colin R.; Tacchetti, Carlo; Valetti, Caterina
Summary Little is known as to how cells ensure that organelle size and number are coordinated to correctly couple organelle biogenesis to the demands of proliferation or differentiation. OA1 is a melanosome‐associated G‐protein‐coupled receptor involved in melanosome biogenesis during melanocyte differentiation. Cells lacking OA1 contain fewer, but larger, mature melanosomes. Here, we show that OA1 loss of function reduces both the basal expression and the α‐melanocyte‐stimulating hormone/cAMP‐dependent induction of the microphthalmia‐associated transcription factor (MITF), the master regulator of melanocyte differentiation. In turn, this leads to a significant reduction in expression of PMEL, a major melanosomal structural protein, but does not affect tyrosinase and melanin levels. In line with its pivotal role in sensing melanosome maturation, OA1 expression rescues melanosome biogenesis, activates MITF expression and thereby coordinates melanosome size and number, providing a quality control mechanism for the organelle in which resides. Thus, resident sensor receptors can activate a transcriptional cascade to specifically promote organelle biogenesis.